Walking Exercise as an Alternative to Lose Weight and Blood Pressure in Women of Childbearing Age - Erni Juniartati; Zaini, Sarliana; Suhariyanto, Suhariyanto (Window of Health : Jurnal Kesehatan, 2023)
Hypertension or high blood pressure is the Silent Killer that can cause death slowly. Excessive fat accumulation in adipose tissue is obesity that can interfere with individual health. Women who are obese increase every year to 32.9%, caused by lifestyle factors that trigger the risk of obesity. Walking has the advantage of 5M (Mudah or easy, murah or cheap, Meriah or fun, masal or massive, and manfaat or benefits). People can do walking exercises without needing tools or trained people, can do it in groups cheerfully, and get health benefits. This study aimed to determine the effectiveness of walking exercise on body weight and blood pressure in women of reliable age (WUS). The method used a quasi-experimental pre-and post-test design with a control group, and two non-randomly chosen groups were intervention and control groups. The sample consisted of 36 women of reliable age with pre-hypertension, mild hypertension, and overweight and obesity. The results showed a significant difference in systolic and diastolic blood pressure after walking for 30 minutes 5 times a week, p-value 0.000. Walking is also suitable for decreasing Body Mass Index (BMI), with a p-value of 0.000. The conclusion is that walking affects blood pressure and body weight in patients with hypertension and obesity in women of reliable age. It is hoped that further research will provide interventions in a longer time, a larger number of research subjects, and control for other variables that affect blood pressure and BMI in women of childbearing age.